Experimental tests on multiple-slit devices for precast concrete panels. (15th July 2018) - Dal Lago, Bruno; Biondini, Fabio; Toniolo, Giandomenico
Highlights: Multiple Slit Devices (MSDs) are proposed to be used in between precast panels. Monotonic and cyclic tests are carried out on MSDs with different slit shapes. An improved version of the MSD combining plasticity and friction is presented. Panel sub-assembly tests confirm the effectiveness of MSDs in real applications. Design rules for MSDs are proposed. Abstract: Multiple Slit Devices (MSDs) are plasticity-based dissipative connectors consisting of steel plates provided with slits which lead to a set of elementary beams. In this way, the shear-type behavior of the plate is turned into the flexural-type behavior of the elementary beams, which ensures better energy dissipation. The proposed MSDs are bolted to support steel profiles inserted into appropriate recesses in between precast concrete panels to improve the seismic performance of the earthquake-resisting system. The paper presents the results of monotonic and cyclic experimental tests performed on both connectors and structural sub-assemblies consisting of two full-scale precast concrete panels connected by a MSD. Steel plates with slits of various shape and size are considered. An improved version of the connector capable to dissipate energy through both plasticity and friction and to provide enhanced displacement capacity is also proposed and tested.